"The Other Side": Assessing the Polarization of Gender Knowledge Through a Feminist Analysis of the Affective-Discursive in Anti-Feminist Online Communities. (30th August 2020) - Rothermel, Ann-Kathrin
Abstract: Given the current polarization of gender knowledge in the public discourse, this article investigates the "other side" of gender knowledge production. Building on feminist standpoint literature, I conduct a close reading of the affective-discursive dynamics of knowledge production in two anti-feminist online communities in the United States and India. I find that anti-feminist communities appropriate feminist practices of consciousness-raising to construct a shared sense of victimization. This appropriation is, however, incomplete. In contrast to feminist practices, anti-feminist knowledge generation is premised on the polarizing themes of "ultimate victimhood" and "ultimate other, " which lead to violence and exclusion, rather than liberation.